Legal Analysis of Bankruptcy Dispute Resolution Against Boedel Bankruptcy Through Actio Pauliana - Mangatur Ruhut Banuara Sianipar; Ida Nadirah (Yayasan Multidimensi Kreatif, 2025)
In the division of law, bankruptcy and PKPU are included in the scope of civil law. Therefore, the Bankruptcy and Suspension of Debt Payment Obligations Law does not contain any criminal rules at all. Penundaan Kewajiban Pembayaran Utang (PKPU) is regulated in Law No. 37 of 2004, namely in articles 222-294. According to article 222, a Debtor if he is unable or expects to be unable to continue to pay his debt that is due and collectible, may request a postponement of the debt payment obligation. The purpose of postponing debt payment obligations is generally to propose a peace plan that includes an offer to pay all or part of the debt to the Concurrent Creditor, while the purpose is to enable a debtor to continue his business, despite payment difficulties, and or avoid bankruptcy. Bankruptcy is a situation in which the debtor does not make payments on the debts of its creditors. This situation is caused by the difficulty of the financial distress of the debtor's business which has experienced a setback. In Black's Law Dictionary we can see that the definition of bankruptcy is associated with the inability of a person to pay his debts that have become due. Such inability must be accompanied by a concrete action to file, either voluntarily by the debtor himself, or at the request of a third party, an application for a declaration of bankruptcy to the court. One of the efforts to protect creditors in bankruptcy is with Actio Pauliana. Actio Pauliana has since been regulated in Article 1341 of the Civil Code. Actio Pauliana is the right given to a creditor to advance the cancellation of all acts that are not required to be done by the debtor, while the debtor knows that by his actions the creditor is harmed. This right is a protection provided by law for creditors against the debtor's actions that can harm creditors.